Lime Effectiveness of Crab Shell Powder in Acid Spodosols - ADILOGLU, AYDIN; ADILOGLU, SEVINC (Asian Journal of Chemistry, 2010)
This study was carried out in order to determine the effects of increasing crab shell powder on some macro and trace elements content of acid soils. For this purpose, 5 acid Spodosols were used according to US Taxonomy. The incubation experiment was done under laboratory conditions with 3 replications. Four different doses of crab shell powder (0, 5000, 10000 and 15000 kg ha-1) were applied to each pot and incubated for 2 and 4 months. According to the results, pH value, available P content and exchangeable Ca and Mg contents of soils increased with increasing of crab shell powder application and time. But, organic matter amount, exchangeable K content and available trace element (Fe, Cu, Zn and Mn) contents of acid soils decreased with increasing of crab shell powder application and time. All these increases and decreases, except Zn content, were statistically significant at the confidence level of 1 %.